1991
DOI: 10.1139/l91-008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometric data collection and interpretation in the prairie provinces and Northwest Territories

Abstract: This paper outlines the current status of the hydrometric network of the Prairie provinces and the Northwest Territories, the data and information available, general hydrologic characteristics of the region, and efforts being made to ensure that the network continues to meet the needs of Canadians in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Then, by the late 1950s, the Canadian hydrometric network doubled to ∼1250 stations and then expanded to 3000 stations by 1975 as the International Hydrological Decade (1965–1974) brought global attention to the need for hydrometric data. However, by the late 1980s the federal network was not meeting the minimum gauging station density suggested by the WMO in some regions across Canada [ Perks et al , 1991; Letvak , 1994]. Instead of continued growth of the Canadian hydrometric network, cuts to the network were beginning to appear by the early 1990s because of increased budget pressures.…”
Section: Decline In Hydrometric Network Density: Examples Of Canada Amentioning
confidence: 99%
“…Then, by the late 1950s, the Canadian hydrometric network doubled to ∼1250 stations and then expanded to 3000 stations by 1975 as the International Hydrological Decade (1965–1974) brought global attention to the need for hydrometric data. However, by the late 1980s the federal network was not meeting the minimum gauging station density suggested by the WMO in some regions across Canada [ Perks et al , 1991; Letvak , 1994]. Instead of continued growth of the Canadian hydrometric network, cuts to the network were beginning to appear by the early 1990s because of increased budget pressures.…”
Section: Decline In Hydrometric Network Density: Examples Of Canada Amentioning
confidence: 99%
“…According to the World Meteorological Organization (WMO, 2008), the hydrometeorological network does not necessarily have to be full-scale but it should be such as to maximize information content. In a study conducted by Perks et al (1991) on the adequacy of hydrometeorological observations in Canada, WMO noted that the minimum required density was not reached in the mountainous and inland regions, where densities were only one-fifth to one-third of those recommended by WMO. The density of hydrometeorological stations in the central Himalayan region of Nepal is low, with most located in valley bottoms and in areas that are easily accessible and populated (Barros, Joshi, Putkonen, & Burbank, 2000).…”
Section: Adequacy Of Hydrometeorological Observation Network and Quamentioning
confidence: 99%
“…A number of studies also found that the Canadian National Hydrometric Network (CNHN) density is below the World Meteorology Organization (WMO) minimum standards [ Perks et al ., ; Letvak , ; Coulibaly et al ., ]. Since its establishment in the 1890s, the CNHN has always been below the WMO recommendations for minimum network density [see Mishra and Coulibaly , ; Perks et al ., ; Letvak , ]. A recent study by Coulibaly et al .…”
Section: Introductionmentioning
confidence: 99%